One-Pot-Multicomponent Synthesis of 2,6-Diamino-4-arylpyridine-3,5-dicarbonitrile Derivatives Using Nanomagnetic Fe3O4@SiO2@ZnCl2 - Behrooz Maleki; Hadi Natheghi; Vahid Sokhanvaran; Samaneh Sedigh Ashrafi (Indonesian Journal of Chemistry, 2018)
Nanomagnetic Fe3O4@SiO2@ZnCl2 was used as a simple, cost-effective, and reusable heterogeneous catalyst for the synthesis of 2,6-diamino-4-arylpyridine-3,5-dicarbonitriles by a one-pot-three-component condensation reaction of malononitrile, ammonium acetate, and aldehydes under solvent-free conditions at 110 °C. Simple and mild reaction conditions, facile preparation of the catalyst, the use of a cheap catalyst and easy workup and isolation are notable features of this method.